Pengaruh Pendidikan Akhlak terhadap Perilaku Siswa di Sekolah MAN 3 Medan - Aidin, Winda; Jannah, Raudhatul; Sagala, Ardin Rizky Andre; Nasution, Abdul Fattah (Indo-MathEdu Intellectuals Journal, 2025)
Moral education, which includes Islamic moral and ethical values, is integrated into the school curriculum through various methods, including lectures, discussions, and extracurricular activities. This study aims to evaluate the effect of moral education on student behavior at MAN 3 Medan School. This study uses a mixed approach, namely quantitative with surveys and qualitative through in-depth interviews through surveys analyzed using descriptive and inferential statistics. Descriptive statistics are used to describe the distribution and tendency of data, such as averages, medians, and percentages. The results of the study indicate that moral education has a significant impact on improving students' positive behavior. Students involved in the moral education program showed improvements in aspects of discipline, honesty, responsibility, and tolerance and empathy. In addition, moral education also helps reduce negative behaviors such as disobedience and disrespectful behavior. This study emphasizes the importance of integrating moral education into the school curriculum to shape the character of students with noble character. Educational institutions are advised to continue to strengthen moral education programs with innovative and relevant approaches, and involve the entire school community, including teachers, students, and parents.